2001
DOI: 10.1029/2000wr900295
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and potential of commercially available rhodamine WT as a groundwater tracer

Abstract: Abstract. We conducted chemical characterization, batch, column, and modeling studies to elucidate the sorption and transport of rhodamine WT (RWT) in the subsurface. The sand-pack material from the Lizzie field site near Greenville, North Carolina, served as our porous media. Our study confirms earlier results that RWT consists of two isomers with different sorption properties. It also shows that the two isomers have distinct emission spectra and are equally distributed in the RWT solution. The presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…We used RWT as a conservative tracer in this study in spite of evidence that under some circumstances sorption and photo-degradation may cause RWT to act nonconservatively, resulting in poor tracer recovery (Sutton et al 2001). However, in wetlands with limited sediment-water exchange and short residence times (less than a week), recoveries are sufficient for RWT to be useful in studies of hydrologic residence (Lin et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…We used RWT as a conservative tracer in this study in spite of evidence that under some circumstances sorption and photo-degradation may cause RWT to act nonconservatively, resulting in poor tracer recovery (Sutton et al 2001). However, in wetlands with limited sediment-water exchange and short residence times (less than a week), recoveries are sufficient for RWT to be useful in studies of hydrologic residence (Lin et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Thorough laboratory research on the RWT sorption characteristics has shown that the extent of sorption is dependent on different factors such as sediment type, organic matter concentration, initial RWT concentration, pH, ionic strength and the ionic composition of the solution [4,[9][10][11][12]. In addition, RWT is made up of two isomers [4,9,10] with different sorption properties and different emission spectra, which are equally distributed in RWT solution.…”
Section: Rhodamine Wtmentioning
confidence: 99%
“…In addition, RWT is made up of two isomers [4,9,10] with different sorption properties and different emission spectra, which are equally distributed in RWT solution. Isomer 1 (para) is an almost conservative tracer, while isomer 2 (meta) is a nonconservative tracer due to its sorption to sediments [4,9,10].…”
Section: Rhodamine Wtmentioning
confidence: 99%
“…However, RWT has been found to adsorb to many subsurface media (Sabatini & Austin 1991;Shiau et al 1993) because one of the two major isomers in commercially available rhodamine WT, isomer 2, can be significantly and irreversibly adsorbed (Shiau et al 1993). A few studies have evaluated the usefulness of RWT as a groundwater tracer in porous media (Sabatini & Austin 1991;Difazio & Vurro 1994;Sutton et al 2001;Harden et al 2003). However, no evaluation has been done for pumice sand aquifer media.…”
Section: Introductionmentioning
confidence: 99%